Effect of instant ear domes on real-ear gain - Salma Samy Attia; Hesham Kozou; Doaa Elmoazen (The Egyptian Journal of Otolaryngology)
Abstract Purpose As instant ear domes are the most commonly used fittings for RIC hearing aids and are available in standard sizes and shapes which may include vents, this study was designed to assess the acoustics of these different types of domes by estimating the insertion loss and vent effect of each using real-ear measurements to make the right fitting choice. Methods The study included 30 normal hearing individuals. REM procedures specifically insertion loss and vent effect measurements were obtained using Affinity 2.0 Interacoustics while using five types of domes: open, tulip, Bass 1 vent, Bass 2 vent, and double dome. The subjective occlusion rating of each dome was assessed as well. Results The instant ear domes are arranged from least occluding (lowest insertion loss, highest vent effect, lowest subjective rating score) to most occluding (highest insertion loss, lowest vent effect, highest subjective rating score) as follows: open dome, tulip dome, and bass group which showed no significant difference between 1 and 2 vents and lastly double dome. Results showed high variability. Conclusions Instant domes with larger vent whether a single large diameter or sum of several diameters vent have lowest insertion loss, highest vent effect and lowest score in subjective occlusion ratings, and vice versa. Individualized real-ear measurement should be considered for best fitting outcome.